1991
DOI: 10.1037/0022-3514.61.1.115
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of depression and posttraumatic stress symptoms after a natural disaster: The 1989 Loma Prieta earthquake.

Abstract: Measures of emotional health and styles of responding to negative moods were obtained for 137 students 14 days before the Loma Prieta earthquake. A follow-up was done 10 days again 7 weeks after the earthquake to test predictions about which of the students would show the most enduring symptoms of depression and posttraumatic stress. Regression analysis showed that students who, before the earthquake, already had elevated levels of depression and stress symptoms and a ruminative style of responding to their sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
2,032
8
42

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,560 publications
(2,137 citation statements)
references
References 13 publications
55
2,032
8
42
Order By: Relevance
“…However, one study with an early measurement time suggested that depressive symptoms did not influence PTSD, while acute stress symptoms predicted depressive symptoms (Fu et al, 2017). Another study with pretrauma data showed that depression was not significantly different between 14 days before and 10 days after the earthquake or between 14 days before and seven weeks after the earthquake among undergraduate survivors but that their PTSD scores did differ significantly between 14 days prior to and 10 days after the event (Nolen-Hoeksema & Morrow, 1991). Based on these studies, PTSD symptoms most likely preceded depressive symptoms, and PTSD symptoms most likely affected depressive symptoms in the earliest stage of their relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one study with an early measurement time suggested that depressive symptoms did not influence PTSD, while acute stress symptoms predicted depressive symptoms (Fu et al, 2017). Another study with pretrauma data showed that depression was not significantly different between 14 days before and 10 days after the earthquake or between 14 days before and seven weeks after the earthquake among undergraduate survivors but that their PTSD scores did differ significantly between 14 days prior to and 10 days after the event (Nolen-Hoeksema & Morrow, 1991). Based on these studies, PTSD symptoms most likely preceded depressive symptoms, and PTSD symptoms most likely affected depressive symptoms in the earliest stage of their relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not collect data before the earthquake. An investigation that collected data from 137 undergraduates before the earthquake found that the depression scores of the undergraduate survivors 14 days before the earthquake did not differ significantly from their scores 10 days and seven weeks after the earthquake; however, their PTSD scores did differ significantly between 14 days prior to and 10 days after the event (Nolen-Hoeksema & Morrow, 1991). Furthermore, in terms of therapy, Meyer, Kimbrel, Tull, and Morissette (2011) found that treatments for PTSD tended to decrease symptoms of depression, whereas treatments for comorbid disorders such as depression did not necessarily decrease symptoms of PTSD (Meyer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This was operationalized by a Ruminative Response Scale-score ≥ 43 (RRS; Nolen-Hoeksema & Morrow, 1991). 53 participants responded to the invitation (27%), completed the baseline assessment and were randomly assigned to a CCT or VST.…”
Section: Methods Participantsmentioning
confidence: 99%
“…The tendency to respond to a stressor with rumination was assessed using the Ruminative Response Scale (RRS-NL-EXT; Nolen-Hoeksema & Morrow, 1991;Treynor et al, 2003). In addition to a rumination total score, the RRS-NL-EXT provides a Brooding and a Reflection subscale, of which Brooding is viewed as the most maladaptive form of rumination (Joormann et al, 2006;Treynor et al, 2003).…”
Section: Questionnairesmentioning
confidence: 99%
“…With regards to worry, all eleven studies measuring worry used the Penn State Worry Questionnaire (PSWQ; Meyer et al, 1990). Regarding rumination, five studies used the Response Styles Questionnaire (RSQ; Nolen-Hoeksema & Morrow, 1991); two studies used the Rumination-reflection questionnaire (RRQ; Trapnell & Campbell, 1999); one study used the Rumination on Sadness Scale (RSS; Raes, Hermans, & Eelen, 2003); one study used the Daily Emotion Report (DER; NolenHoeksema, Morrow & Fredrickson, 1993); and one study created their own items. Foa & Meadows (1997) suggest the use of treatment protocol manuals to ensure consistency and all studies in this review satisfied this standard.…”
Section: Treatment Integrity Of Included Studiesmentioning
confidence: 99%